Optimization of single strand DNA incorporation reaction by Moloney murine leukaemia virus reverse transcriptase. (11th June 2018) - Ohtsubo, Yoshiyuki; Sasaki, Haruna; Nagata, Yuji; Tsuda, Masataka
Abstract: In this study, we investigated CIS reaction (c lamping-mediated i ncorporation of single-stranded DNA with concomitant DNA s yntheses) of Moloney murine leukaemia virus reverse transcriptase (MMLV-RT), and established a set of conditions with which single-stranded DNA is ligated to a G-tailed model substrate DNA at efficiencies close to 100%. Prior to the CIS reaction, a target blunt-end DNA was 3′ G-tailed by MMLV-RT in the presence of a tailing enhancer, deoxycytidine. In the CIS reaction, the G-tail reacted with a single-stranded DNA carrying a stretch of Cs on its 3′ end (termed as GAO for g uide a daptor o ligonucleotide), and MMLV-RT performed DNA polymerization, starting from the 3′ overhang, using the GAO as a template. We could append a given nucleotide sequence of as long as 72 nucleotides, which would be sufficient for various NGS-sequencing platforms. The high efficiency and the unique features of this MMLV-RT activity that enables the labelling of each DNA molecule with a unique degenerate sequence as a molecular identifier has many potential uses in biotechnology.